Recent advances in Hodge theory period domains, algebraic cycles, and arithmetic - Kerr, Matt 1975-; Pearlstein, Gregory 1970- (London Mathematical Society lecture note series, 2016)
Papers from the summer school and conference: Recent advances in Hodge theory : period domains, algebraic cycles, and arithmetic; held from June 10-20, 2013, at the Pacific Institute of Mathematical Sciences, University of British Columbia, Vancouver, Canada